Internalisasi Etos Kerja Islam : Perspektif Aktualisasi Iman - Nafis Irkhami; Ningsih, Puji Lestari (Jurnal Ilmiah Ekonomi Islam, 2025)
The phenomenon of the weak implementation of Islamic work ethics among Muslims—despite being the largest religious group in Indonesia—deserves serious attention. Building a strong national economy requires a society of high quality and strong work ethics. However, the concept of Islamic work ethics remains unfamiliar or underapplied by many Muslims themselves. There is even a misconception that Islamic work ethics is separate from acts of worship and not part of one’s obligation to serve Allah. In practice, Islamic work ethics is often not integrated with ritual worship and is neglected in everyday work life. This study recommends strengthening Islamic work ethics by raising awareness of faith and religiosity in the professional sphere. Thus, Islamic work ethics becomes part of righteous deeds (amal shalih) that Muslims strive to carry out as a manifestation of their faith in Allah. Using a qualitative approach and literature review method, this study finds that in Islam, work ethics is not merely a social necessity but an integral part of faith and righteous action that must be internalized and actualized. Islamic work ethics is born from the awareness that work is a form of worship with deep spiritual value. Therefore, faith that is actualized through Islamic work ethics plays a strategic role in shaping a productive, ethical, and socially responsible society—becoming a cultural force that promotes national progress. Keywords: Faith actualization, Internalization, Islamic work ethics, Righteous deeds,